Anti-adhesive therapies as a contemporary means to fight infectious diseases and adherence factors of Corynebacteria diphtheriae - Yelyseyeva, I; Babych, Ye; Zhdamarova, L; Belozersky, V; Isayenko, Ye; Kolpak, S (Annals of Mechnikov's Institute, 2020)
The emergence and increasing prevalence of bacterial strains that cause infectious diseases and that are resistant to available antibiotics demand the discovery of new therapeutic strategies. For many pathogenic bacteria, infections are initiated only after the organism has first adhered to the host cell surface. A modern alternative approach to antimicrobial therapy is targeting bacterial virulence and specifically adhesion as one of virulence factors. This approach forms the basis of anti-adherence strategies, which have been devised to prevent a variety of bacterial infections. The article deals with some modern strategies for anti-adhesion therapy, the mechanisms of inhibition pathogen adherence, immunization using a bacterial adhesion, an adhesin subunit or an immunogenic peptide fragment and a DNA vaccine encoding the adhesin or part thereof and so on. Investigation of bacterial pili which orchestrate the colonization of host tissues is the area most in need of further study. Bacterial pili may be vaccine candidates in important human pathogens as being highly immunogenic structures which are under the selective pressure of host immune responses. C. diphtheriae, the causative agent of diphtheria, is well-investigated in respect to toxin production, while little is known about its factors crucial for colonization of the host. Adherence factors of Corynebacteria may be considered as probable components of developing of combined diphtheria vaccines with antibacterial action which localizes a diphtheritic infection in an organism. They’ll become an effective method against a resistant carrier state and be forward to stopping of pathogen circulation among human population.